2015
DOI: 10.1038/srep07923
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate addition enhanced soil inorganic nutrients to a large extent in three tropical forests

Abstract: Elevated nitrogen (N) deposition may constrain soil phosphorus (P) and base cation availability in tropical forests, for which limited evidence have yet been available. In this study, we reported responses of soil inorganic nutrients to full factorial N and P treatments in three tropical forests different in initial soil N status (N-saturated old-growth forest and two less-N-rich younger forests). Responses of microbial biomass, annual litterfall production and nutrient input were also monitored. Results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
4
14
0
Order By: Relevance
“…As with the study by Zhou, et al 20. on acorn leaf stoichiometric traits, some elemental concentrations and ratios of both acorn seeds and weevil larvae differed significantly between P-rich sites and P-deficient sites, likely due to the differences in soil P, Ca, Mg, Fe, Mn and Al between the two site types1220 (Figs 3, 4 and 6 and 7, Supplementary Tables S1, S2, S3 and S4). This suggests stoichiometric plasticity of both plants and their parasite in response to elemental variability in the environment4, as well as a strong influence of soil elements on different trophic organisms along a food chain.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…As with the study by Zhou, et al 20. on acorn leaf stoichiometric traits, some elemental concentrations and ratios of both acorn seeds and weevil larvae differed significantly between P-rich sites and P-deficient sites, likely due to the differences in soil P, Ca, Mg, Fe, Mn and Al between the two site types1220 (Figs 3, 4 and 6 and 7, Supplementary Tables S1, S2, S3 and S4). This suggests stoichiometric plasticity of both plants and their parasite in response to elemental variability in the environment4, as well as a strong influence of soil elements on different trophic organisms along a food chain.…”
Section: Discussionsupporting
confidence: 74%
“…For example, P rich soils have lower C:P and nitrogen (N):P ratios in plants8, higher P composition in plants910 and higher P and RNA content and population density of herbivore ( Sabinia setosa )11. The higher soil inorganic nutrients (N, P, potassium (K), calcium (Ca), magnesium (Mg))12 on P rich sites may also lead to reduced locust outbreaks that occur more often on N-deficient soils13. Long-term adaptation to nutritional differences and resultant differentiation in stoichiometric composition helps ecotype formation1415.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Aciego Pietri and Brookes [24] concluded that soil pH had marked effects on microbial biomass through affecting the availability of biologically toxic Al and organic C solubility. In our study, the pH in the HP treatment was increased by 0.43 unit (from 4.92 to 5.35) compared to the control, which was in line with previous studies suggesting P addition increased soil base cations via stimulation on litter nutrient input and eventually elevated soil pH [9,10]. All in all, these results imply that soil pH may be another factor affecting soil microbial biomass in the HP treatment.…”
Section: Figsupporting
confidence: 80%
“…To date, multiple mechanisms have been proposed to explicate the P effects on soil microbes [e.g., 3,5,7,9] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%